Self-Compassion and Resilience at Work: A Practice-Oriented Review. Issue 4 (November 2020) - Lefebvre, Jade-Isis; Montani, Francesco; Courcy, François
The Problem: A key challenge for human resource development (HRD) scholars and practitioners is to understand the individual competences that can be trained and developed to enhance employee resilience at work. Empirical evidence has been accumulated on the benefits of self-compassion—that is, a set of malleable states that can be developed through HRD interventions—for individual resilience, as well as on the factors that can strengthen self-compassion in organizations. Nonetheless, limited efforts have been devoted to translate this critical scientific knowledge into evidence-based, practical insights that could guide the implementation of effective human resource development practices to develop self-compassion and, thereby, increase resilience in organizations. The Solution: This article presents a practice-oriented literature review of the benefits of self-compassion for resilience at work. The relationship between self-compassion and resilience at work, as well as the specific workplace factors that foster growth are outlined for practical implications in the workplace. Facilitators are identified as (1) personal factors (i.e., experience of stress and level of self-awareness), (2) contemplative trainings, and (3) leadership styles and listening styles. This article provides evidence-based practical recommendations for the implementation of these factors and of self-compassion in organizations for increased resilience. The Stakeholders: Stakeholders of this practice-oriented review are employees (especially those exposed to highly stressful job conditions) and their leaders, human resource developers in charge of setting the development of training and developmental processes to enhance self-compassion and resilience, and HRD research scholars interested in advancing current literature on self-compassion and resilience at work.